Association of Celiac Disease and Inflammatory Bowel Disease: A Nationwide Register-Based Cohort Study. (25th September 2022) - Mårild, Karl; Söderling, Jonas; Lebwohl, Benjamin; Green, Peter H.R.; Pinto-Sanchez, Maria Ines; Halfvarson, Jonas; Roelstraete, Bjorn; Olén, Ola; Ludvigsson, Jonas F.
Abstract : INTRODUCTION: To determine the risk of inflammatory bowel disease (IBD) in patients with celiac disease (CeD) (and vice versa ) compared with general-population comparators. METHODS: Using Swedish histopathology and healthcare register data, we identified 48, 551 patients with CeD and 83, 529 with IBD diagnosed in 1969–2016. Each patient was compared with age- and sex-matched general-population comparators (CeD: n = 240, 136; IBD: n = 408, 195). Cox regression estimated hazard ratios (HRs) for IBD in patients with CeD and vice versa . Our main analyses were limited to events beyond the first year of follow-up to reduce potential surveillance bias. RESULTS: During follow-up, 784 (1.6%) patients with CeD were diagnosed with IBD compared with 1, 015 (0.4%) matched comparators. In patients with CeD, the HR for IBD was 3.91 (95% confidence interval [CI] 3.56–4.31), with largely similar HRs for Crohn's disease (4.36; 3.72–5.11) and ulcerative colitis (3.40; 3.00–3.85). During follow-up, 644 (0.8%) patients with IBD and 597 (0.1%) comparators were diagnosed with CeD. The HR for CeD in patients with IBD was 5.49 (95% CI 4.90–6.16), with the highest risk estimates seen in ulcerative colitis (HR = 6.99; 6.07–8.05), and the HR for Crohn's disease was 3.31 (2.69–4.06). In patients with CeD and IBD, the diagnostic interval was usually <1 year; however, HRs of 3–4 were seen even after 10 years of follow-up. During 20 years of follow-up, 2.5% of patients with CeD developed incident IBD, and 1.3% of patients with IBD developed CeD. DISCUSSION: The bidirectional association between CeD diagnosis and IBD warrants attention in the initial assessment and follow-up of these conditions. Their co-occurrence, independent of temporal sequence, suggests shared etiology.